[RETRACTED ARTICLE] Surrogates’ Decision Making Process Regarding Treatments for Critically IllElderly Muslim Patients at the End Stage of Life - Jehloh, Latifah; Nilmanat, Kittikorn; Kongsuwan, Waraporn (Princess of Naradhiwas University Journal, 2019)
This article has been Retracted at the request of the Editor-in-Chief. This descriptive research aimed to study the steps in thedecision-making processfrom surrogates regarding treatment for critically ill patients at the ending stage of life, in a Muslim cultural context. Conveniencesampling was used to select 120 surrogates of patients from Muslim cultural background who have been treated in the internal medicine intensive care unit and medical ward in 5 southern province hospitals. Information collected consisted inquestionnaires on demographic data, as well as on 3 different decision-making processes. Alpha’s Cronbach coefficient for instrument was 0.87. Descriptive statistics was used for data analysis. Results revealedthatstep of the decision-making process regarding information acknowledgement; asking about symptom information, was rated the most (M = 3.28, S.D. = 1.06), followed by disease prognosis (M = 3.14, S.D. = 1.05). In the step of data analysis, religious belief was rated the most (M = 3.98, S.D. = 0.03), followed by patients’ needs (M = 3.94, S.D. = 0.06), identify the criteria in decision and alternatives in treatment (M = 3.75, S.D. = 0.48), as well as analysis of family relationship after the decision making(M = 3.46, S.D. = 0.71). Surrogate decision-makers did all steps of the decision-making process. Findings from this study might be useful to develop guidelines to provide health information to support decision making and to develop care plan that is consistent with cultural context and background of patients and family.